The rise and stall of a fair trade pioneer: The Cafedirect story - Davies, Iain A.; Doherty, B; Knox, Simon (Springer Science Business Media, 2010)
This is a case study investigating the growth of fair trade pioneer, Cafédirect. We explore the growth of the company and develop strategic insights on how Cafédirect has attained its prominent position in the UK mainstream coffee industry based on its ethical positioning. We explore the marketing, networks and communications channels of the brand which have lead to rapid growth from niche player to a mainstream brand. However, the company is experiencing a slow down in its meteoric rise and we question whether it is possible for the company to regain its former momentum with its current marketing strateg